Avalanche Characteristics of AlxGa1-xN Avalanche Photodiodes - Ooi, Tat Lung Wesley; Cheang, Pei Ling; You, Ah Heng; Chan, Yee Kit (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2021)
AlGaN APDs are ultra-wide-bandgap semiconductor which has great potential, especially UV detection. In this work, Monte Carlo model has been developed to simulate the avalanche characteristics of thin AlxGa1-xN APDs with random ionization path lengths incorporating dead space effect in a wide range of x value. Holes dominate the impact ionization at higher field for Al0.3Ga0.7N, whereas electrons dominate the impact ionization for Al0.7Ga0.3N. Al0.3Ga0.7N also has higher electron and hole ionization coefficients compared to Al0.7Ga0.3N. Hole-initiated multiplication leads the mean multiplication gain for Al0.3Ga0.7N APDs, while electron-initiated multiplication leads the mean multiplication gain for l0.7Ga0.3N APDs. The breakdown voltage and excess noise at fixed mean multiplication gain of 10 and 20 are then compared. The breakdown voltage increases as the Al content increases. The excess noise of hole-initiated multiplication is the lowest at x ≈ 0.4 while excess noise of electron-initiated multiplication is lowest at x = 0.7. This shows that the ideal Al content is at x ≈ 0.4 as the excess noise is low with manageable breakdown voltage as excess noise for hole-initiated multiplication decreases as x approaching 0.4.